2020
DOI: 10.1016/j.celrep.2020.108079
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin 2 in Macrophages Links Mitochondrial ROS Production, Cytokine Release, Phagocytosis, Autophagy, and Bactericidal Activity

Abstract: Highlights d In macrophages, LPS-induced ROS production requires mitochondrial mitofusin 2 d Mfn2 is required for the production of cytokines, phagocytosis, and antigen processing d Survival from bacterial infection or septic shock is compromised in Mfn2 À/À mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 81 publications
(87 reference statements)
7
83
3
Order By: Relevance
“…Although the previous study showed that MFN2 deficiency results in a decreased phagocytosis in macrophages 12 , we did not observe any difference of Mtb phagocytosis between Mfn2 WT and Mfn2 CKO macrophages. The discrepancy might be due to different receptor–ligand interactions in macrophages between previous studies 12 and ours. Our data are also partly consistent with previous findings that MFN2 was required for IL-1β secretion during infection with RNA viruses 11 .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Although the previous study showed that MFN2 deficiency results in a decreased phagocytosis in macrophages 12 , we did not observe any difference of Mtb phagocytosis between Mfn2 WT and Mfn2 CKO macrophages. The discrepancy might be due to different receptor–ligand interactions in macrophages between previous studies 12 and ours. Our data are also partly consistent with previous findings that MFN2 was required for IL-1β secretion during infection with RNA viruses 11 .…”
Section: Discussioncontrasting
confidence: 99%
“…We found that myeloid cell-specific MFN2 is essential for antimicrobial and inflammatory responses in vitro and in vivo during intracellular bacterial infection. These data partly correlate with a recent study reporting the protective role for myeloid MFN2 in innate immune responses during sepsis and bacterial infection 12 . Although the previous study showed that MFN2 deficiency results in a decreased phagocytosis in macrophages 12 , we did not observe any difference of Mtb phagocytosis between Mfn2 WT and Mfn2 CKO macrophages.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations